EVALUASI KEBIJAKAN SOP KEPOLISIAN TENTANG MASA DEMOSTRASI DALAM PENGAMANAN KEPOLISIAN DI POLRES KOTA TERNATE - Albertus Mabel; Riswanda; Abdurrahman Kader (ADMIN: Jurnal Administrasi Negara, 2024)
Democracy demands a basic ideological agreement, order and freedom, so that in political struggle democracy has an important meaning for the people who use it because with democracy the people's right to determine the course of government organizations according to their wishes can be guaranteed. Efforts made by the police to deal with anarchic demonstrations can be carried out through non-penal or penal measures. In handling it, in general the public tends to judge the police SOP as not humanistic because they carry out anarchic actions. However, it turns out that the police have special rules that regulate this as stated in the Regulation of the Chief of the Indonesian National Police No. 9 of 2008 (Perkapolri 9/2008) concerning Procedures for Organizing, Serving, Securing and Handling Cases for Expressing Opinions in Public. This is intended to ensure that the demonstration can run well and in an orderly manner, so that things do not harm the community and then notify the relevant agencies in advance which will be the target of the demonstration and/or demonstration. In carrying out repressive actions, the police must carry out actions in accordance with (protap). This action was taken because the situation was no longer conducive and it was no longer possible to prevent it, so the police needed to take this action to anticipate so that the impact of the riot did not spread, as regulated in police protocol number 1 of 2010 concerning dealing with anarchy. Then the Police also made several efforts, namely by increasing the professionalism of Police members, coordinating with related agencies and providing legal education to the community.